Profile of Problem Solving Systems in Linear Equations of Three Variabels of Class X Students in Terms of Mathematical and Gender Anxiety Based in MAN 2 Palu - Rina, Rina; Bennu, Sudarman; Sukayasa, Sukayasa (Jurnal Riset Pendidikan MIPA, 2020)
This research is a qualitative study which aims to obtain a description of the profile of problem solving systems in linear equations of three variables of the Islamic student madrasah in terms of mathematical and gender anxiety based on Polya's steps. The subjects of this study were male and female students of class X who had severe and mild math anxiety. The results of this study are (1) When understanding mathematical problems, the LB subject reads the voice slowly but can still be heard, the whole slowly, many times and often asks, PB subjects read in a rather loud voice, all slowly, many times -times and often asking questions, the subject of LR reads in a low voice, slowly, word for word, the subject of PR does a sound reading rather loudly, slowly, and repeatedly; (2) When compiling a problem-solving plan, LB and PB subjects plan to use a combined method, look nervous, impatient, and ask many questions, LR subjects using substitution methods are relatively more patient and calm in finding solutions, PR subjects plan to use a combined method , relatively more patient and calm in finding solutions; (3) when carrying out the problem solving plan, LB and PB subjects tend to be restless, in a hurry and need a relatively long time and do not write the completion steps completely, the subject of LR and PR tends to be quiet, silent, not saying much words and requires a relatively short time and write down the completion steps completely; (4) when re-examining the results of work, the subject of LB and PB checks the results of the answers obtained by verification only once and often asks, the subject of LR and homework re-check the results of answers obtained through repeated verification three times to feel confident with the answer.